Influence of fibre reinforcement on the post-cracking behaviour of a cement-stabilised sandy-clay subjected to indirect tensile stress - Cristelo, Nuno (2017)
An experimental campaign was carried out to determine the influence of polypropylene fibre content and length on the post-cracking response of a sandy-clay stabilised with different cement contents. Three main sets of specimens were prepared: cement-stabilised specimens with two cement contents (5% and 10%); fibre-reinforced specimens with three fibre contents (0.1%, 0.2% and 0.3%) and cement-fibre-reinforced specimens combining the mentioned fibre and cement contents. Tensile tests on the fibres and indirect tensile tests and triaxial compression tests on the prepared specimens were conducted. Results show that the post-cracking behaviour is strongly affected by the combination of fibre and cement content as well as fibre length. Pull-out was the governing failure mode. Post-peak tension loss rate increased with fibre content, as a result of the loss of influence of the fibres on the post-peak behaviour. On the contrary, an increase in fibre content resulted in higher pre-peak strength gain rates and higher peak stresses.